Development of a Community-Based Multi-Grade Learning Unit to Enhance Communication Skill and Collaboration Skill among Grade 1 and 2 Students - Ngasantia, Prapasiri; Jongkonklang, Sirinat (Ratchaphruek Journal, 2025)
The research was aimed to 1) develop Community-Based Multi-Grade Learning Unit among grade 1 and 2 students 2) study the quality of Community-Based Multi-Grade Learning Unit on the following aspects; compare learning achievement before and after learning, compare learning achievement after learning and the 70 percent criterion, compare students’communication skill before and after learning and compare students’ collaboration skills before and after learning. The sample group was 16 students of grade 1 and 2 students from Ban Prasat School. Cluster random sampling was used to choose the sample. The research tools were the learning unit with 4 lesson plans, achievement test, and communication skill and collaboration skill assessment form. The data were analyzed by the percentages, mean, standard deviation, t-test, and Wilcoxon signed-rank test. The results of the study indicated that: learning unit comprises unit title, learning objectives, learning evidence, instructional design, and lesson plans, which was assessed to be at the highest level of appropriateness and alignment. Study the quality of Community-Based Multi-Grade Learning Unit on the following aspects; learning achievement was significantly higher than before learning at .05 level, learning achievement was higher than the 70 percent criteria with no statistically significant at .05 level, communication skill of grade 1 and 2 students was significantly higher than before learning at .05 level and collaboration skill of grade 1 and 2 students was significantly higher than before learning at .05 level.